Hubungan Gaya Hidup (Lifestyle) dengan Kejadian Hipertensi pada Usia Produktif: The Relationship of Lifestyle with Hypertension in Productive Age - Marlita Marlita; Rizki Muji Lestari; Fitriani Ningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Hypertension is a disease with a prevalence increasing every year. WHO data declared hypertension is one of the premature death in the whole world. Hypertension factors are because of consumption of so much salt, less physical activity, and smoking. The incidence of hypertension in 2019 has 472.618 cases. Then based on the data DINKES Kalimantan Tengah Province of 2020, hypertension cases decreased by 374.093. Then based on the data of DINKES Palangka Raya City in 2019 and 2020, hypertension has ranked the two diseases most high in Palangka Raya City, with 10.337 cases in 2019 and rising in 2020 to 16.935 cases. The Purpose: The study determined the relationship of lifestyle with hypertension at productive age. Method: The study used design methods Literature Review. Data source with a google scholar (2017-2020). The article used the Indonesia Language. Strategy using the PICOS with criteria Inclusion and Exclusion. Results: The study showed that six articles in the analysis state a relationship between lifestyle and hypertension at productive age. The factors include consumption of excess salt, less physical activity, and smoking. Conclusion: Based on the six articles about the relationship of lifestyle with hypertension in productive age, the consumption of so much salt, less physical activity, and smoking. The consumption of salt leads to increased blood volume, which impacts the onset of hypertension. Less physical activity tends to have a faster heart rate, and cardiac muscles work harder, which affects hypertension. And smoking, the nicotine in tobacco, is the cause of increased blood pressure.